2019
DOI: 10.1002/adom.201900121
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Optimization of All‐Dielectric Magnetic Nanoantennas

Abstract: Magnetic light and matter interactions are generally too weak to be detected, studied, and applied technologically. However, if one can increase the magnetic power density of light by several orders of magnitude, the coupling between magnetic light and matter could become of the same order of magnitude as the coupling with its electric counterpart. For that purpose, photonic nanoantennas, in particular dielectric, are proposed to engineer strong local magnetic field and therefore increase the probability of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…In Ref. [60], the authors identified the optimal configuration of a binary configuration, made of Si and air, which maximizes the magnetic field intensity. The geometry and its binary representation are shown in Figure 5a, in which each "1" represents Si rectangular meta-atoms and each "0" represents an air void.…”
Section: Genetic Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ref. [60], the authors identified the optimal configuration of a binary configuration, made of Si and air, which maximizes the magnetic field intensity. The geometry and its binary representation are shown in Figure 5a, in which each "1" represents Si rectangular meta-atoms and each "0" represents an air void.…”
Section: Genetic Algorithmmentioning
confidence: 99%
“…So far, our discussion has focused on the optimization of only a single target in the objective function. A more challenging [60] Copyright 2019, Wiley-VCH. d-f): another example to illustrate the usefulness of utilizing evolutionary approach based technique in enhancing near field intensity.…”
Section: Genetic Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the striking increment of the multi-dimensional parameter spaces in the metasurfaces designs, the realization of some highperformance metasurfaces becomes time-consuming, such as the high-NA, high-efficiency metalens, and the ultra-wideband multifunctional meta-devices. Recently, the development of AI techniques has become a research hot spot, and enables novel microwave and photonic devices, which may relieve the researchers from tedious trials and errors-testing works [155][156][157][158][159][160][161][162][163]. For example, a topology-optimized method was applied to optimize the phase design of the metalens [164].…”
Section: Artificial Intelligence Aided Metalensmentioning
confidence: 99%
“…Topology optimization employs a robust numerical algorithm to seek the layout of materials within the design domain, so as to minimize or maximize the defined objective function [36]. Topology optimization has been proven to be an efficient and effective tool for the design of PCs [37][38][39][40][41][42][43][44][45][46]. Here, we will extend topology optimization to design the unit cell of nontrivial and trivial PCs for SPTIs.…”
Section: Inverse-design Approachmentioning
confidence: 99%